AlN metal–semiconductor field-effect transistors using Si-ion implantation. (6th March 2018) - Okumura, Hironori; Suihkonen, Sami; Lemettinen, Jori; Uedono, Akira; Zhang, Yuhao; Piedra, Daniel; Palacios, Tomás
Abstract: We report on the electrical characterization of Si-ion implanted AlN layers and the first demonstration of metal–semiconductor field-effect transistors (MESFETs) with an ion-implanted AlN channel. The ion-implanted AlN layers with Si dose of 5 × 10 14 cm −2 exhibit n-type characteristics after thermal annealing at 1230 °C. The ion-implanted AlN MESFETs provide good drain current saturation and stable pinch-off operation even at 250 °C. The off-state breakdown voltage is 2370 V for drain-to-gate spacing of 25 µm. These results show the great potential of AlN-channel transistors for high-temperature and high-power applications.